Turkey : Selected Issue. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses key issues of Turkey's economy including private savings in Turkey, increase in the minimum wage for 2016, and nonfinancial corporate sector debt in Turkey. Over the last decade and half, Turkey successfully stabilized its macro economy. In the aftermath of the 1999-2001 economic crises, Turkey pursued a highly successful policy of macroeconomic stabilization. At the same time, however, private sector saving rate decreased significantly, leading to a current account deficit. The minimum wage increased by 30 percent in January 2016, affecting about 8 million workers directly. Nonfinancial corporate sector debt has increased substantially in recent years, on the back of increased foreign currency leverage.